2015
DOI: 10.1002/pros.22979
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase in multidrug-resistant enteric bacilli blood stream infection after prostate biopsy-A 10-year population-based cohort study

Abstract: Multidrug-resistant enteric bacilli are becoming a problem in Sweden, despite low antimicrobial use. Men need to be informed about the increasing risks of infectious complications of transrectal prostate biopsy. One out of 50 men undergoing a prostate biopsy will develop symptoms suggestive of a bloodstream infection after the biopsy and one in 100 men will have a positive blood culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…Biomarker analysis typically requires tissue biopsy, which is invasive, may involve inadequate sampling of heterogeneous tumors, and can be associated with patient discomfort and risk for complications (3)(4)(5)(6)(7)(8). Tissue biopsy is also not routinely feasible for longitudinal measurement of biomarkers in patients undergoing treatment.…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Biomarker analysis typically requires tissue biopsy, which is invasive, may involve inadequate sampling of heterogeneous tumors, and can be associated with patient discomfort and risk for complications (3)(4)(5)(6)(7)(8). Tissue biopsy is also not routinely feasible for longitudinal measurement of biomarkers in patients undergoing treatment.…”
Section: Implications For Patient Carementioning
confidence: 99%
“…However, although very high PSA values indicate a high probability of cancer detection by biopsy, lower values poorly discriminate PCa from inflammatory processes and benign hyperplasia ( Ploussard et al , 2013 ; Hayes and Barry, 2014 ). On the basis of the results of two large epidemiological studies showing a very small or no effect of PSA testing on PCa mortality ( Andriole et al , 2012 ; Schroder et al , 2012 ) and the negative consequences of PSA screening, which include overdiagnosis, overtreatment and treatment complications, the US Preventive Services Task Force recommended against the use of PSA testing for PCa screening ( Aly et al , 2015 ; Johnson et al , 2015 ).…”
mentioning
confidence: 99%
“…The number of cases increased from two to 18, before and after the year 2010, respectively. 65 A prospective multicenter study conducted in Turkey showed that 19% of 400 men undergoing PNB carried ESBL-producing organisms. 66 Presence was significantly associated with concurrent diabetes and previous fluoroquinolone usage ( P <0.05).…”
Section: Special Considerationsmentioning
confidence: 99%